Ответ:
[tex]\bf a)\ \ (3-b)^3=(3-b)(3-b)(3-b)\\\\b)\ \ (3a+2)^3=(3a+2)(3a+2)(3a+2)[/tex]
P.S. Если надо раскрыть скобки, то
применяем формулы : [tex]\bf (x\pm y)^3=x^3\pm 3a^2b+3ab^2\pm y^3[/tex] .
[tex]\bf (3-b)^3=27-3\cdot 9\cdot b+3\cdot 3\cdot b^2-b^3=27-27b+9b^2-b^3\\\\(3a+2)^3=27a^3+3\cdot 9a^2\cdot 2+3\cdot 3a\cdot 4+8=27a^3+54a^2+36a+8\\\\\\Formyla:\ \ \bf x^3\pm y^3=(x\pm y)(x^2\pm xy+y^2)\\\\c)\ \ 3^3+b^3=(3+b)(9-3b+b^2)\\\\d)\ \ a^3-4^3=(a-4)(a^2-4a+16)[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Ответ:
[tex]\bf a)\ \ (3-b)^3=(3-b)(3-b)(3-b)\\\\b)\ \ (3a+2)^3=(3a+2)(3a+2)(3a+2)[/tex]
P.S. Если надо раскрыть скобки, то
применяем формулы : [tex]\bf (x\pm y)^3=x^3\pm 3a^2b+3ab^2\pm y^3[/tex] .
[tex]\bf (3-b)^3=27-3\cdot 9\cdot b+3\cdot 3\cdot b^2-b^3=27-27b+9b^2-b^3\\\\(3a+2)^3=27a^3+3\cdot 9a^2\cdot 2+3\cdot 3a\cdot 4+8=27a^3+54a^2+36a+8\\\\\\Formyla:\ \ \bf x^3\pm y^3=(x\pm y)(x^2\pm xy+y^2)\\\\c)\ \ 3^3+b^3=(3+b)(9-3b+b^2)\\\\d)\ \ a^3-4^3=(a-4)(a^2-4a+16)[/tex]